Sequence analysis and potentials of the native RbcS promoter in the development of an alternative eukaryotic expression system using green microalga Ankistrodesmus convolutus - Thanh, Tran; Chi, Vu Thi Quynh; Omar, Hishamuddin; Abdullah, Mohd Puad; Napis, Suhaimi (MDPI AG, 2012)
The availability of highly active homologous promoters is critical in the development of a transformation system and improvement of the transformation efficiency. To facilitate transformation of green microalga Ankistrodesmus convolutus which is considered as a potential candidate for many biotechnological applications, a highly-expressed native promoter sequence of ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit (AcRbcS) has been used to drive the expression of β-glucuronidase (gusA) gene in this microalga. Besides the determination of the transcription start site by 5¢-RACE, sequence analysis revealed that AcRbcS promoter contained consensus TATA-box and several putative cis-acting elements, including some representative light-regulatory elements (e.g., G-box, Sp1 motif and SORLIP2), which confer light responsiveness in plants, and several potential conserved motifs (e.g., CAGAC-motif, YCCYTGG-motifs and CACCACA-motif), which may be involved in light responsiveness of RbcS gene in green microalgae. Using AcRbcS promoter::gusA translational fusion, it was demonstrated that this promoter could function as a light-regulated promoter in transgenic A. convolutus, which suggested that the isolated AcRbcS promoter was a full and active promoter sequence that contained all cis-elements required for developmental and light-mediated control of gene expression, and this promoter can be used to drive the expression of heterologous genes in A. convolutus. This achievement therefore advances the development of A. convolutus as an alternative expression system for the production of recombinant proteins. This is the first report on development of gene manipulation system for unicellular green alga A. convolutus.